PENGARUH METODE DEEP BACK MASSAGE TERHADAP INTENSITAS NYERI PADA PERSALINAN KALA I (Jurnal Kesehatan Siliwangi, 2022)
The normal delivery process is the process of expelling the products of conception (fetus and placenta) that have been enough months or can live outside the womb. This labor process will cause contractions. Every woman in labor wants the pain of childbirth not to cause pain so that women do not experience birth trauma. Various methods of pain relief, both pharmacological and non-pharmacological that can reduce labor pain, one of which is the deep back massage technique. This technique is carried out on mothers who have entered labor by massaging the mother's sacrum area so that the pain that the mother experiences can be reduced. This Evidence-Based Case Report (EBCR) aims to determine the effect of deep back massage on reducing the intensity of labor pain in the first stage. The method used in writing EBCR is by tracing evidence through a database from Pubmed. Inclusion criteria: articles using English, published in 2016 to 2021, research design in articles is Random Clinical Trial (RCT), systematic review and or meta-analysis, and journals can be accessed in full (full text). The deep back massage technique is carried out in the mother's sacrum area for 20 minutes and this can reduce the intensity of pain during the first stage of labor. The conclusion is that deep back massage can reduce the intensity of pain in the first stage of labor. Key words: Deep Back Massage, first stage labor pain, Sacral Massage